Prenatal intention to human milk feed in the native Hawaiian population: predictors of any human milk feeding from birth to six months postpartum - Méabh Murray; Jessie Kai; Amanda Dentinger; Leah Kaplan; Meliza Roman; Eileen O'Brien; John Kearney; Bliss Kaneshiro; Fengqing Zhu; Marie K. Fialkowski (BMC, 2024)
Abstract Background Rates of non-communicable diseases are disproportionately high among Native Hawaiian (NH) people, and the proportion of NH infants being fed human milk (HM) is the lowest among all ethnicities within the state of Hawaiʻi. The aim of this study was to explore biological, socio-economic, and psychosocial determinants of the initiation and duration of human milk feeding (HMF) among a study of NH mothers and infants. Methods A sample of 85 NH mother-infant dyads who were participating in a larger prospective study were involved in this research. Recruitment for the parent was delayed due to the COVID-19 pandemic. Recruitment started in November 2020 and continued until April 2022. Questionnaires were distributed at birth, two-months, four-months, and six-months postpartum. Questionnaires addressed topics relating to maternal and infant characteristics and infant feeding practices. Descriptive statistics, comparative analysis, and multivariate logistic regression tests were conducted. Results The majority of participating mothers were aged between 31 and 35 years, had some college education or more, were employed, and multiparous. The majority of infants were receiving HM at each timepoint (94% at birth, 78% at two-months postpartum, and 76% at four and six-months postpartum). Factors found to be significantly associated with HMF initiation and duration were prenatal intention to HMF, maternal educational attainment, Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) participation, and Supplemental Nutrition Assistance Program (SNAP) recipiency. A prenatal intention to HMF was found to be a strong predictor of HMF at birth (aOR = 64.18, 95% CI 2.94, 1400.28) and at two-months postpartum (aOR = 231.55, 95% CI 2.18, 2418.3). Participants not involved with WIC were more likely to be HMF at four-months postpartum (aOR = 6.83, 95% CI 1.01, 46.23). Conclusion This research supports existing evidence that prenatal intention to HMF and higher maternal educational attainment are positive predictors of HMF. WIC participation and being a SNAP recipient were found to be negatively associated with HMF which suggests a need for more culturally tailored support. Further research is required to reduce the gap in knowledge related to the determinants of HMF in NH.